Tipologi Pemikiran Ali Syariati Konsepsi Agama, Politik dan Sosial - miftakhur ridlo (Pena Islam Jurnal Pendidikan Agama Islam, 2019)
The offer of Shari'ah Islamic thoughts and ideologies became the fourth bridge or path from the integrity of the ideology of the pre-revolutionary opposition movement, namely secular nationalism, Communist Marxism and Islamic fundamentalism. In Shariati's revolutionary Islamic ideology various groups of sects and ideologies united as a mass force against the shah of the Shah. Technically Shari'ati ideology was socialized through speeches, sermons and public lectures which were always attended by thousands of supporters. Shariati's ideology paved the way for the acceptance of Imam Khomeini as a revolutionary leader. All contradictions such as atheist Marxism versus politically impotent Islam, foreign modernity versus debilitating nativism or religious meditations against secular meditations have been removed by Shariati as unnecessary misunderstandings. The true pattern of Shi'ite religions, namely the Shia Alawi, as promoted by Ali Shariati, is able to unite Iranians in the struggle for liberation.